2024
DOI: 10.1002/ccd.31088
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends with the Evolut family of self‐expanding transcatheter heart valves: A single‐center experience

Ilan Merdler,
Brian C. Case,
Sukhdeep Bhogal
et al.

Abstract: BackgroundThe Evolut self‐expanding valve (SEV) systems (Medtronic), were designed to accommodate varying valve sizes and reduce paravalvular leak (PVL) while maintaining a low delivery profile. These systems have evolved between product generations, alongside valve deployment techniques changing over time.Aims:This study aimed to examine whether these changes impacted clinical outcomes.MethodsEPROMPT is a prospective, investigator‐initiated, postmarketing registry of consecutive patients undergoing transfemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…overlap technique to allow higher implantation-appear to have modestly reduced the pacemaker implantation rate in most studies, 1,3 this reduction was not observed in the study by Merdler et al 2 The Merdler study tells us that that TAVR outcomes certainly can improve as technical advances and implantation techniques change, but the continued high rate of pacemaker implantation remains an issue with self-expanding valve systems. Even with the newest generation Evolut FX (Medtronic) system, the in-hospital pacemaker implantation rate was 11.9%, 4 significantly higher compared to the newest generation balloon-expandable valve system (5.6%), 5 attributed to the continuous radial force exerted on the conduction system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…overlap technique to allow higher implantation-appear to have modestly reduced the pacemaker implantation rate in most studies, 1,3 this reduction was not observed in the study by Merdler et al 2 The Merdler study tells us that that TAVR outcomes certainly can improve as technical advances and implantation techniques change, but the continued high rate of pacemaker implantation remains an issue with self-expanding valve systems. Even with the newest generation Evolut FX (Medtronic) system, the in-hospital pacemaker implantation rate was 11.9%, 4 significantly higher compared to the newest generation balloon-expandable valve system (5.6%), 5 attributed to the continuous radial force exerted on the conduction system.…”
mentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions, Merdler et al2 analyzed their single-center experience of TAVR using a self-expanding valve system. A total of 300 patients who underwent TAVR from January, 2018 through November, 2021 were divided into three equal groups (January 2018 to October 2018: 100 patients, November 2018 to July 2020: 100 patients, August 2020 to November 2021: 100 patients).…”
mentioning
confidence: 99%